Rumen tissue histology of Nellore cattle submitted to either nutritional restriction or intake of concentrate feedstuffs prior to adaptation period - Reis, B. [UNESP] (2018)
Sao Paulo State Univ UNESP, Anim Sci Coll, Dracena, SP, Brazil